Caracterización y evaluación de un nuevo sistema de fijación vertebral lumbar - Castellanos Vera, José Raúl (My University, 2013)
Caracterización y evaluación de un nuevo sistema de fijación vertebral lumbar
Caracterización y evaluación de un nuevo sistema de fijación vertebral lumbar
Keywords: Caracterización y evaluación de un nuevo sistema de fijación vertebral lumbar